Papilloma dan Karsinoma Sinonasal - Rizki Hanriko; Muhartono Muhartono (Jurnal Kesehatan, 2017)
Sinonasal papilloma is rare, only 0.5-4% of sinonasal tumors with aetiopathogenesis has not known yet. Sinonasal carcinoma is a rare malignancy, and the most common types are squamous cell carcinoma (SCC). Malignant transformation of papilloma is very low, which inverted type were reported about 2-27%, with the development of papilloma into carcinoma was approximately 63 months (6 months-13 years). Prior study showed the malignant transformation in 11% of recurrences inverted papilloma, which were 7%syncronous and 3.6% metachronous SCC. The unilateral inverted papilloma with sinonasal squamous cell carcinoma were usually occured in the elderly. Some factors to consider in malignant transformation of papilloma were recurrence, atypical features and HPV. Smoker, large tumor and lesion in the frontal sinus area were had a tendency to recurrence. Malignancy were associated with bone invasion, bilateral inverted papilloma, squamous cell hyperplasia, presence of three types of epithelial cells (squamous metaplasia, squamous mature and cylindrical cell), heavy hyperkeratosis, mitotic index ≥2/HPF, the absence of polyps inflammation, the number of plasma cells, low of eosinophils and neutrophils absent.